2019
DOI: 10.1097/01.apo.0000578944.25956.8b
|View full text |Cite
|
Sign up to set email alerts
|

Myopia: Anatomic Changes and Consequences for Its Etiology

Abstract: The process of emmetropization is the adjustment of the length of the optical axis to the given optical properties of the cornea and lens after the end of the second year of life. Up to the end of the second year of life, the eye grows spherically. Axial elongation in the process of emmetropization after the second year of life is associated with a thinning of the retina and a reduced density of retinal pigment epithelium (RPE) cells in the equatorial and retroequatorial region, and a thinning of the choroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 64 publications
(75 reference statements)
0
46
0
1
Order By: Relevance
“…A main feature of an axially elongated eye is an increased degree of fundus tessellation, which is also strongly correlated with a decreasing thickness of the SFCT (Yan et al, 2015). Other features of an increasing axial elongation in non-highly myopic eyes include a shift of the Bruch's membrane (BM) opening, usually into the temporal direction, leading to an overhanging of BM into the intrapapillary compartment at the nasal optic disk and, correspondingly, an absence of BM at the temporal disk border in the form of a parapapillary gamma zone; an ovalization of the ophthalmoscopically detectable optic disk shape and a decrease in the ophthalmoscopical horizontal disk diameter due to the temporal BM shift; and an increase in the disk-fovea distance due to the development of parapapillary gamma zone and, correspondingly, a decrease in the angle kappa between the two temporal vascular arcades (Jonas et al, 2015(Jonas et al, , 2017(Jonas et al, , 2019Guo et al, 2018). In view of this long list of axial elongation-associated morphological changes in the posterior fundus, it might have been expected that besides ophthalmologists, also deep-learningbased algorithms can estimate axial length.…”
Section: Discussionmentioning
confidence: 99%
“…A main feature of an axially elongated eye is an increased degree of fundus tessellation, which is also strongly correlated with a decreasing thickness of the SFCT (Yan et al, 2015). Other features of an increasing axial elongation in non-highly myopic eyes include a shift of the Bruch's membrane (BM) opening, usually into the temporal direction, leading to an overhanging of BM into the intrapapillary compartment at the nasal optic disk and, correspondingly, an absence of BM at the temporal disk border in the form of a parapapillary gamma zone; an ovalization of the ophthalmoscopically detectable optic disk shape and a decrease in the ophthalmoscopical horizontal disk diameter due to the temporal BM shift; and an increase in the disk-fovea distance due to the development of parapapillary gamma zone and, correspondingly, a decrease in the angle kappa between the two temporal vascular arcades (Jonas et al, 2015(Jonas et al, , 2017(Jonas et al, , 2019Guo et al, 2018). In view of this long list of axial elongation-associated morphological changes in the posterior fundus, it might have been expected that besides ophthalmologists, also deep-learningbased algorithms can estimate axial length.…”
Section: Discussionmentioning
confidence: 99%
“…The optic nerve head canal consists anatomically of three layers: the Bruch's membrane opening (BMO), the opening in the choroidal layer delineated by the peripapillary border tissue of the choroid (Jacoby), and the scleral flange opening, covered by the lamina cribrosa and delineated by the peripapillary border tissue of the scleral flange (Elschnig). 1 , 2 Recent studies have revealed that, with axial elongation in moderately myopic eyes, the BMO shifts from its original position backward, usually into the temporal direction toward the fovea. 3 This leads to an overhanging of Bruch's membrane (BM) into the intrapapillary compartment at the nasal disc border, as well as a lack of BM in the temporal parapapillary region, referred to as a gamma zone.…”
mentioning
confidence: 99%
“…A widely accepted view is that the mechanical elongation of the eyeball due to excessive axial elongation may be contributory to the development of PRC. Starting at the equator, the sclera thinning is most marked at the posterior pole owing to the axial elongation occurring in the course of myopization [28]. It is speculated that scleral thinning results from the mechanical elongation caused by axial elongation since the scleral volume showed no obvious increase during the process of myopization, which is accompanied by the remodeling of existing scleral tissue [29].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the FRT was shown not to be signi cantly different among the three groups. It was reported that the occurrence of retinal thinning in the equatorial and retroequatorial region was attributed to a tube-like enlargement of the eyeball, and retinal thickness in the macular region was irrelevant to axial length [28], which may explain the lack of association between FRT and PRC. It should be emphasized that choroidal thickness of all subjects were measured after cyclopegia in our study.…”
Section: Discussionmentioning
confidence: 99%